2021
DOI: 10.1001/jamanetworkopen.2021.14336
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Genomic Newborn Screening Programs

Abstract: IMPORTANCE Genomic newborn screening (gNBS) may optimize the health and well-being of children and families. Screening programs are required to be evidence based, acceptable, and beneficial. OBJECTIVES To identify what has been discovered following the reporting of the first gNBS pilot projects and to provide a summary of key points for the design of gNBS. EVIDENCE REVIEW A systematic literature review was performed on April 14, 2021, identifying 36 articles that addressed the following questions: (1) what is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 62 publications
2
48
0
Order By: Relevance
“…The BabySeq Project is a series of randomized controlled trials of whole exome sequencing (WES) in newborns from the newborn nursery (NBN) or intensive care unit (ICU) who were randomized to conventional care plus family history assessment and genetic counseling alone or with WES. Detailed methodology for the study design and recruitment can be found elsewhere 1,2 . In brief, parents and newborns from the well-baby nursery at Brigham and Women’s Hospital (BWH) and parents and sick newborns from the neonatal intensive care unit and other intensive care units (NICU/ICUs) at BWH, Boston Children’s Hospital (BCH), and Massachusetts General Hospital (MGH), were approached, consented, and enrolled into the study regardless of the absence or presence of a specific phenotype.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BabySeq Project is a series of randomized controlled trials of whole exome sequencing (WES) in newborns from the newborn nursery (NBN) or intensive care unit (ICU) who were randomized to conventional care plus family history assessment and genetic counseling alone or with WES. Detailed methodology for the study design and recruitment can be found elsewhere 1,2 . In brief, parents and newborns from the well-baby nursery at Brigham and Women’s Hospital (BWH) and parents and sick newborns from the neonatal intensive care unit and other intensive care units (NICU/ICUs) at BWH, Boston Children’s Hospital (BCH), and Massachusetts General Hospital (MGH), were approached, consented, and enrolled into the study regardless of the absence or presence of a specific phenotype.…”
Section: Methodsmentioning
confidence: 99%
“…Recent advances in the clinical deployment of genome-scale sequencing now make it possible to determine an infant’s complete genome sequence shortly after birth, enabling the identification of deleterious variants associated with monogenic disorders along with other health-related traits 1 . Genomic sequencing as a screening tool in newborns is being explored 2 and supplementary genomic screening panels are now offered by several commercial laboratories 3 , but there are a number of evidentiary, ethical, and cost concerns that must be considered 1,4-7 .…”
mentioning
confidence: 99%
“…This may be done through the expansion of genomic and/or other technologies, and by reviewing the evidence required to incorporate conditions in screening programs in the context of a national publicly-funded health system ( Genetic Alliance UK, 2022 ). Other genomic population screening research initiatives have taken place or are underway internationally, and highlight the importance of equitable access, managing expectations and uncertainties, and ensuring a robust consent process ( Screen4care, 2022 ; Holm et al, 2018 ; Roman et al, 2020 ; Downie et al, 2021 ). However, there remains a relative lack of empirical evidence about the benefits and harms of these programs, particularly in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advantages, the use of WGS in newborn screening at a national health system level is a novel approach and limitations remain, particularly when testing asymptomatic rather than pre-symptomatic individuals. For example, it will be important to minimize feedback of information that is uncertain or not clinically useful, and the burden this may place on families and health systems ( Nuffield Council on Bioethics, 2017 ; Biesecker et al, 2021 ; Downie et al, 2021 ). The sensitivity, specificity, positive and negative predictive values would be expected to vary for each condition depending on its prevalence, ability to distinguish pathogenic from benign variants, and ability to detect known and unknown pathogenic variants ( Hagenkord et al, 2020 ; Marshall et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The advent of new genetic technologies and potential therapies has led to renewed interest in newborn screening for rare disorders, 7 including genetically determined neurodevelopmental disorders for which early detection may benefit affected newborns and their families. Individuals affected by PWS, AS, or Dup15q may benefit from newborn screening followed by early targeted interventions that may become available in the next 5 years.…”
Section: Introductionmentioning
confidence: 99%